Surveillance of antibiotic resistance among common Clostridium difficile ribotypes in Hong Kong. Issue 1 (December 2017) - Chow, Viola; Kwong, Thomas; So, Erica; Ho, Yolanda; Wong, Sunny; Lai, Raymond; Chan, Raphael
Abstract Incidence ofClostridium difficile infection (CDI) is rapidly increasing and it poses a major health burden globally. However, data regarding the epidemiology of CDI in Asia are limited. We aimed to characterize the antimicrobial susceptibility patterns of common ribotypes of toxigenicC. difficile in Hong Kong. Fifty-three PCR ribotypes were identified among 284 toxigenicC .difficile clinical isolates. The five most prevalent ribotypes were 002 (13%), 017 (12%), 014 (10%), 012 (9.2%), and 020 (9.5%). All testedC .difficile strains remained susceptible to metronidazole, vancomycin, meropenem and piperacillin/tazobactam, but highly resistant to cephalosporins. Of the fluoroquinolones, highest resistance to ciprofloxacin was observed (99%), followed by levofloxacin (43%) and moxifloxacin (23%). The two newly emerged PCR ribotypes, 017 and 002, demonstrated high levels of co-resistance towards clindamycin, tetracycline, erythromycin and moxifloxacin. PCR ribotypes 017 and 002 with multi-drug resistance are rapidly emerging and continuous surveillance is important to monitor the epidemiology ofC. difficile to prevent outbreaks of CDI.